Identification of High Potential Person (HIPO) pada Fatigue Risk Management Operasi Perusahaan Pertambangan - Patmasari Patmasari; Dadan Erwandi (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2026)
Fatigue among heavy equipment operators is a major occupational risk that contributes significantly to workplace accidents in the mining industry. High workload demands, extended working hours, and shift systems particularly night shifts substantially increase fatigue risk. This study aimed to examine the relationship between operator fatigue and workplace accidents and to evaluate the effectiveness of fatigue risk management through the High Potential Person (HIPO) program. An observational analytic study with a cross-sectional design was conducted using secondary data collected from the Defender and Jigsaw fatigue monitoring systems between January and August 2025. The study population comprised all 947 active heavy equipment operators at PT Petrosea, Kideco Jaya Agung site, and total sampling was applied. Descriptive and analytical analyses were performed to assess the distribution of fatigue incidents, accident occurrences, and their associations. The findings revealed that fatigue incidents were more prevalent during night shifts, and operators experiencing repeated fatigue events had a significantly higher risk of workplace accidents. The implementation of fatigue risk management strategies including real-time fatigue monitoring, identification of HIPO operators, shift scheduling adjustments, and targeted preventive interventions effectively reduced repeated fatigue incidents. This study highlights the critical role of systematic fatigue risk management in improving occupational safety and enhancing operational productivity in the mining sector.